English Language Needs of Electrical Engineering Students: A Journal-Based ESP Perspective - Asti Gumartifa; Indah Windra Dwie Agustiani (English Language in Focus (ELIF), 2026)
The purpose of this study is to examine Electrical Engineering students’ perceptions of essential English skills and the conceptualization of learning needs and goals within a journal-based ESP context related to academic and professional demands. This study employed a descriptive qualitative design involving 35 Electrical Engineering students enrolled in a one-semester English course. The learning process was structured into six meetings through group discussions and presentations based on English-language journal article texts aligned with the syllabus. Data were collected through interviews and a Likert-scale questionnaire to address the research questions. The results revealed that 80.7% of students participated in the English course to improve their English-speaking skills, although 48% still identified speaking as their primary learning difficulty. Journal article-based ESP learning functions as a pedagogical strategy that shapes students' perceptions of English learning needs and goals in alignment with academic and professional demands. These findings highlight the need to reconceptualize ESP curriculum design by positioning discipline-specific academic practices through reading activities. The findings also contribute to improving students’ English speaking and reading skills to support academic learning processes in higher education.